Methods of using EHMT2 inhibitors in treating or preventing blood disorders - RAIMONDI, Maria Alejandra; GIBAJA, Veronica; PENEBRE, Elayne (2024)
The present disclosure relates to a method of preventing or treating a blood disorder (e.g., sickle-cell disease) via administering an EHMT2 inhibitor compound disclosed herein or a pharmaceutical composition thereof to subjects in need thereof. The present disclosure also relates to the use of such compounds for research or other non-therapeutic purposes.